2003
DOI: 10.1603/0022-0493-96.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bifenthrin Treatment Zones Against Red Imported Fire Ant

Abstract: Exclusion of ants, particularly red imported fire ant, Solenopsis invicta (Buren), from homes, nursing facilities, hospitals, and electrical housings is an important strategy in urban and rural pest control. We conducted a laboratory bioassay to determine the repellency of granular bifenthrin (Talstar: rate 2.087 kg of formulated product/92.88 m2 or 4.6 lb formulated product/1000 feet2 or 4.2 g active ingredient/92.88 m2) to S. invicta foragers. In the field, we compared the efficacy of three widths (0.3, 2.0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Different control strategies require toxicants with different sets of properties. To maximize efÞcacy of baits, the active ingredient should have delayed toxicity and be transferable and nonrepellent (Stringer et al 1964), whereas repellent or fast-acting toxicants are effective barriers (Pranschke et al 2003). The purpose of this study was to evaluate contact insecticides for topical toxicity, knockdown rate, horizontal toxicity, contact toxicity, and barrier effects against the Argentine ant.…”
mentioning
confidence: 99%
“…Different control strategies require toxicants with different sets of properties. To maximize efÞcacy of baits, the active ingredient should have delayed toxicity and be transferable and nonrepellent (Stringer et al 1964), whereas repellent or fast-acting toxicants are effective barriers (Pranschke et al 2003). The purpose of this study was to evaluate contact insecticides for topical toxicity, knockdown rate, horizontal toxicity, contact toxicity, and barrier effects against the Argentine ant.…”
mentioning
confidence: 99%
“…Neoh et al, found after exposed to chlorantraniliprole termitea were likely to cease feeding and undergo starvation, which made the pesticide low efficiency 35 . Because in the management of social insect, repellent or fast-acting toxicant may provide effective barriers 36 . Non-radiolable rubidium (Rb) have been used as a good trace in termites' trophallaxis process [37][38][39] , but had not yet been reported in S.invicta.…”
Section: Discussionmentioning
confidence: 99%
“…Contact insecticides are commonly used in controlling the red imported Þre ants, Solenopsis invicta Buren. Numerous contact insecticides have been tested by broadcast application (Blake et al 1959, Lofgren et al 1961, Reinert 1998, individual mound treatment (Appel and Woody 1990, Reinert andMaranz 1996, Jones et al 1998), and zone treatment (Pranschke et al 2003). In broadcast application and individual mound treatments using contact insecticide, contact between ant and insecticide is required for the treatments to be effective.…”
mentioning
confidence: 99%